2018
DOI: 10.1002/micr.30365
|View full text |Cite
|
Sign up to set email alerts
|

Immediate tracheal reconstruction with forearm flap and bone graft

Abstract: Creating a tracheostoma during the first operation prevents postoperative airway compromise. Our bone graft placement easily achieves tracheal rigidity. This procedure is simple and safe for tracheal window defect repair.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 30 publications
(83 reference statements)
1
2
0
Order By: Relevance
“…In our study, postoperative stenosis was not observed clinically or on tracheoscopy at follow-up. Comparing the findings of our study with those of other series on patients with TC using different techniques, the SCM periosteal flap seemed superior to free flaps and secondary closure in terms of achieving a stable airway [13][14][15][16][17][18] with a low percentage of permanent tracheostomies. Series of ETE anastomoses or sleeve resections showed good results in terms of establishing a stable airway; however, many of the results demonstrated non-negligible mortality [19][20][21] and morbidity 20,[22][23][24] due to complications ( Table 2).…”
Section: Surgical Notessupporting
confidence: 65%
“…In our study, postoperative stenosis was not observed clinically or on tracheoscopy at follow-up. Comparing the findings of our study with those of other series on patients with TC using different techniques, the SCM periosteal flap seemed superior to free flaps and secondary closure in terms of achieving a stable airway [13][14][15][16][17][18] with a low percentage of permanent tracheostomies. Series of ETE anastomoses or sleeve resections showed good results in terms of establishing a stable airway; however, many of the results demonstrated non-negligible mortality [19][20][21] and morbidity 20,[22][23][24] due to complications ( Table 2).…”
Section: Surgical Notessupporting
confidence: 65%
“…In the literature, the myoperiosteal SCM flap, described by Friedman et al 39 and used for reconstruction of the trachea after WR, has been referred to as a soft tissue flap, muscle flap or a perichondrial flap 17,35,93,94,99,100 , which does not take into consideration the flap´s potential for calcification and the subsequent stability of the reconstructed trachea. This possible misinterpretation has often led to this technique being referred to in the same way as other reconstructive alternatives, although it has a different outcome on the patency of the airway and surgical morbidity and mortality.…”
Section: Thyroid Cancer Invading the Tracheamentioning
confidence: 99%
“…We vertically inserted the rib cartilage into a pocket immediately below the dermis of the skin flap. Kubo reported the effectiveness of this procedure using a forearm flap ( 13 ). As an ALT flap is soft, it is easy to mould it to the irregularly shaped larynx and place trimmed cartilage grafts inside it.…”
Section: Discussionmentioning
confidence: 99%